Substituted hydrocarbon: a CCSD(T) and local vibrational mode investigation. (17th November 2021) - Delgado, Alexis Antoinette Ann; Sethio, Daniel; Matthews, Devin; Oliveira, Vytor; Kraka, Elfi
Abstract : Substituent effects on the carbon–carbon bonds of hydrocarbons have been a topic of interest within the past seven decades as resultant information would enable one to tune the activity of CC bonds. However, current assessments of the C≡C, C=C, and C−C bond strength of acetylene, ethylene, and ethane as well as their derivatives rely on indirect measures such as bond length and bond dissociation enthalpy. In this work, we introduce a quantitative measure of the intrinsic strength of C≡C, C=C, and C−C bonds for a set of 40 hydrocarbon systems consisting of 3 parent structures, 36 hydrocarbon derivatives involving CF3, CH3, CHO, F, NH2, or OH groups, and a conjugated system, based on vibrational spectroscopy. Local mode force constants k a (CC) were computed at the CCSD(T)/cc-pVTZ level of theory for systems 1 –32 and 34 –40 and CCSD(T)/cc-pVDZ for 33 . From k a (CC), we derived related bond strength orders BSO n (CC) in order to provide quantitative measures of intrinsic bond strength. Topological electron density and natural population analyses were carried out as to analyze the nature of these bonds and complement bond strength measures. For substituted hydrocarbon systems, we found the strengthening/weakening of the CC bonds occurs as the covalent nature of the bond increases/decreases by means of varying charge delocalizations. Our findings provide new guidelines for desirably modulating C≡C, C=C, and C−C bond strength and for the design of prospective pathways for bond cleavage reactions. GRAPHICAL ABSTRACT: UF0001